MICROBIOME-HOST INTERACTION AND THEIR IMPACT ON HUMAN HEALTH (Journal of Medical & Health Sciences Review, 2025)
Through metabolic, immune, and neurological interactions, the human microbiome, particularly the gut microbiota, plays a crucial role in maintaining host physiology. These microorganisms have a significant impact on overall health because they help regulate the immune system, digest food, and absorb nutrients. The composition and diversity of the gut microbiome vary across individuals due to genetic, dietary, and environmental factors.  Dysbiosis, a disturbance in the microbial balance, has been linked to a variety of diseases, including metabolic disorders, inflammatory conditions, and neurological problems. Understanding microbiome-host interactions is essential for developing targeted therapeutic interventions.  The human gut microbiome's composition and diversity, as well as the mechanisms by which it affects host physiology and changes in health and disease, are the subjects of this review. A chemist's perspective on the identification and characterization of microbial metabolites and their potential therapeutic applications will also be presented.